2022
DOI: 10.1021/acsami.1c21876
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Multifunctionality of M2+/Imidazole–Etidronates for Proton Conductivity (Zn2+) and Electrocatalysis (Co2+, Ni2+) toward the HER, OER, and ORR

Abstract: This work deals with the synthesis and characterization of one-dimensional (1D) imidazole-containing etidronates, [M 2 (ETID)(Im) 3 ]· n H 2 O (M = Co 2+ and Ni 2+ ; n = 0, 1, 3) and [Zn 2 (ETID) 2 (H 2 O) 2 ](Im) 2 , as well as the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…15,17,32,52 Therefore, it can be clearly pointed out that the partial electron transfer can directly enhance the outstanding bifunctional electrocatalytic performances of the present materials, as evidenced from the pre-and postcatalytic XPS studies. 4,10,13,32,33,52,66,68 Crystallinity and morphology of compound II remain the same as measured by postcatalytic PXRD, SEM, and EDAX analyses (Figures S23 and S24, Supporting Information). Moreover, the present bifunctional electrocatalytic activities are superior compared to that of many hybrid frameworks and other classes of advanced wellexplored electrocatalysts, as evidenced by Tables 1 and S9 and S10 (Supporting Information).…”
Section: ■ Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…15,17,32,52 Therefore, it can be clearly pointed out that the partial electron transfer can directly enhance the outstanding bifunctional electrocatalytic performances of the present materials, as evidenced from the pre-and postcatalytic XPS studies. 4,10,13,32,33,52,66,68 Crystallinity and morphology of compound II remain the same as measured by postcatalytic PXRD, SEM, and EDAX analyses (Figures S23 and S24, Supporting Information). Moreover, the present bifunctional electrocatalytic activities are superior compared to that of many hybrid frameworks and other classes of advanced wellexplored electrocatalysts, as evidenced by Tables 1 and S9 and S10 (Supporting Information).…”
Section: ■ Introductionmentioning
confidence: 69%
“…In recent years, researchers are mainly focused to fabricate such electrocatalysts based on different classes of framework materials such as metal–organic frameworks (MOFs), hybrid open-frameworks, as well as different metal oxides, hydroxides, sulfides, nitrides, phosphides, and phosphonates. Among them, transition-metal phosphonates can be considered as one of the most effective electrocatalysts, owing to their structural diversity, tunable morphology, long-term stability, and cost-effective generation. …”
Section: Introductionmentioning
confidence: 99%
“…These results agree with the low thermodynamic stability of histidine‐metal complexes at applied potentials, as widely studied in imidazole‐based HER electrocatalysts. [ 33–37 ] Tafel plots in Figure 3d also confirm the role of carboxylates in stabilizing the Zn 2+ coordination and preventing HER, while introducing a large amount of histidine destabilizes the Zn 2+ coordination. The Tafel curves showed that ZnCND and 50%H‐ZnCND‐anchored anode had much lower current density over a wider voltage range from −1.5 V to −1.9 V (vs Ag/AgCl) than that of pure Zn, suggesting slower HER kinetics with the labile interphase.…”
Section: The Effect Of Labile Interphase‐coordinated Modulation On De...mentioning
confidence: 61%
“…The Tafel slope value of 68 mV dec −1 suggested the Volmer−Heyrovsky mechanism associated with the reaction, in which hydrogen adsorption and discharge steps are rate-determining steps (Figure 6b). 31,65 The HER catalytic stability was examined by chronoamperometric measurement at an applied potential of −0.15 V vs RHE for 24 h (Figure 6c). Ni x Co 1−x @Ni x Co 1−x O/NCNT revealed a steady current density of approximately 66 mA cm −2 with complete retention of activity.…”
Section: Resultsmentioning
confidence: 97%
“…From LSV, we found that Ni x Co 1 – x @Ni x Co 1 – x O/NCNT showed an overpotential of 74 mV at 10 mA cm –2 , however, the state-of-art Pt/C catalyst showed 33 mV overpotential for achieving the same current density (Figure a). The Tafel slope value of 68 mV dec –1 suggested the Volmer–Heyrovsky mechanism associated with the reaction, in which hydrogen adsorption and discharge steps are rate-determining steps (Figure b). , The HER catalytic stability was examined by chronoamperometric measurement at an applied potential of −0.15 V vs RHE for 24 h (Figure c). Ni x Co 1 – x @Ni x Co 1 – x O/NCNT revealed a steady current density of approximately 66 mA cm –2 with complete retention of activity.…”
Section: Resultsmentioning
confidence: 99%